Pengendalian persediaan berbasis economic order quantity pada UD Wenang Perkasa Manado - Sumba, Selviani; Tirayoh, Victorina Z.; Pinatik, Sherly (Yayasan Widyantara Nawasena Raharja, 2024)
The economic order quantity is the number of goods ordered that will result in the lowest possible cost. This study will determine how inventory control is based on economic order quantity at UD Wenang Perkasa. This study employs a qualitative research method with a descriptive approach. The study results clearly show that the company's total merchandise inventory costs are higher than they would be if they used economic order quantity. This means that using economic order quantity will save the company costs and increase profits. The company must implement economic order quantity as a method for controlling its inventory because it will allow the company to order merchandise in optimal quantities with minimum total inventory costs, increasing the company's profits.